Influence of body composition, muscle strength, diet and physical activity on total body and forearm bone mass in Chinese adolescent girls - Leng, Huat Foo; Qian, Zhang; Kun, Zhu; Guansheng, Ma; Heather, Greenfield; David, R. Fraser (Cambridge University Press, 2007)
The aim of the present study was to determine association between body composition, muscle strength, diet and physical exercise with bone mineral content (BMC) and bone area (BA) in 283 Chinese adolescent girls aged 15 years in Beijing, China. Body composition, pubertal stage, physical activity and dietary intakes were assessed using standard validated protocols. Total body and forearm bone, lean body mass (LBM) and fat body mass (FBM) were determined by dual X-ray absorptiometry. Multivariate linear regression analyses were carried out to examine the predictors of BMC and BA, after controlling for potential confounders. The subjects had a mean age of 15·0 (SD 0·9) years and 99·6% of them had reached menarche. Multivariate analyses showed that LBM, FBM, handgrip muscle strength and milk intake were significant independent determinants of BMC and BA of the total body and/or forearm sites. LBM was found to be a stronger independent determinant than FBM of BMC and BA, whereas handgrip muscle strength was only found as significant determinant of BMC and BA at the forearm sites than in total body BMC and BA. Further, total physical activity level had a significant positive association with handgrip and LBM. This suggested that greater muscle strength and higher LBM may reflect higher levels of physical activity. Therefore, continuous healthy lifestyle practices such as adequate intake of milk and continuous participation in physical activity should be encouraged throughout adolescence to optimise bone growth during this period.